Sosialisasi Literasi dan Sertifikasi Halal untuk Meningkatkan Nilai Produk pada Paguyuban Pedagang Kaki Lima di Kabupaten Kudus - Amaroh, Siti; Husnurrosyidah, Husnurrosyidah (Jurnal Abdi Masyarakat, 2023)
This community service program aims to improve halal literacy and assictance in the halal certification process for street vendors in Kudus regency, Central Java in the form of socialization and focused discussion. The socialization was attended by halal officers from the district ministry of religious affairs, the head of the Kudus street vendors association, the head of regional street vendors association, and graduate students. The approach used is a participatory action approach. The results of the program include: first, the transfer of knowledge about halal, the importance of halal, and the ratification of halal through halal certification to audience. Second, participants understand the law on guaranteeing halal products to provide protection for citizens who are Muslim in consuming food and beverages, medicines, cosmetics, and others. Third, the government and universities understand the problem of steet vendors regarding obstacles in applying for halal certificates. Fourth, street vendors are directed to submit a self-declare, namely a statement letter from the business actor itself regarding the halal status of the traded product